2018
DOI: 10.1007/s10597-018-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Care and Burnout in Individuals Caring for Patients with Alzheimer’s Disease

Abstract: Alzheimer's disease imposes a severe burden upon patients and their caregivers. We examined the relationship between the sociodemographic factors, burden of care and burnout level of 120 of 203 professional caregiving staff dealing with Alzheimer's disease patients in eight geriatric care centers in Istanbul/Turkey. The Zarit Caregiver Burden Scale was used to measure the level of burden of care, and the Maslach burnout inventory to measure the level of burnout. High levels of emotional exhaustion were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…Burnout Syndrome is characterized by a psychosocial syndrome that arises in response to chronic and interpersonal stressors in the workplace. However, it is important to note that this concept is not only related to caregiving load, but also to critical aspects of relationships that the person establishes with his/her occupation 19. This syndrome is characterized by three dimensions: emotional exhaustion (lack of energy and enthusiasm, as well as no emotional resources), depersonalization (adoption of an indifferent, impersonal and even cynical attitude between caregiver and patient), and reduction of personal fulfillment (perceiving care as negative or ineffective) 19…”
mentioning
confidence: 99%
“…Burnout Syndrome is characterized by a psychosocial syndrome that arises in response to chronic and interpersonal stressors in the workplace. However, it is important to note that this concept is not only related to caregiving load, but also to critical aspects of relationships that the person establishes with his/her occupation 19. This syndrome is characterized by three dimensions: emotional exhaustion (lack of energy and enthusiasm, as well as no emotional resources), depersonalization (adoption of an indifferent, impersonal and even cynical attitude between caregiver and patient), and reduction of personal fulfillment (perceiving care as negative or ineffective) 19…”
mentioning
confidence: 99%
“…Moreover, caregivers whose children had lower education indicated higher levels of DP. Yildizhan et al also reported significant connections between caregiver's educational level and perceived EE and DP (Yıldızhan et al 2019). It seems that more educated subjects usually encounter better social interactions, better job opportunities, and income, better problem solving and stress management skills, and greater self-confidence.…”
Section: Discussionmentioning
confidence: 96%
“…Anxiety, agitation, disinhibition, aggressive behavior, sleep problems, the carer being female and the patient's spouse, and social isolation are among the factors that contribute most to an increase in the carer's load (Isik et al, 2019). While a study made in care homes found emotional exhaustion in 25% of caregivers (Yıldızhan et al, 2019), this rate increased to 40% when care was provided by a family member (Truzzi et al, 2012). Many adult children in Turkey caring for their parents suffering from AD feel a responsibility towards their parents, do not trust care homes, and prefer providing care themselves (Ar and Karanci, 2019).…”
Section: Discussionmentioning
confidence: 99%